PENGARUH AFILIASI KELOMPOK BISNIS TERHADAP MANAJEMEN LABA DENGAN KUALITAS AUDIT SEBAGAI MODERASI (Studi Empiris pada Perusahaan Fast Moving Consumer Goods di 5 Negara Emerging Markets ASEAN) - Andi Eko Yuliantoro; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2019)
This study aims to examine the moderating role of audit quality on the association between business group affiliation of firms and earnings management in FMCG companies in 5 emerging markets in ASEAN. In this study, earnings management is proxied by discretionary accruals. Audit quality is measured by two proxies, they are the Big 4 accounting firms and auditor industry specialization. In addition, this study also uses company leverage and loss as a control variable. The population of this study consists of manufacturing companies in the consumer products sector listed in the Bloomberg database in 5 ASEAN countries which are Indonesia, Malaysia, Philippines, Thailand and Vietnam for the period 2017. The method used for sampling is purposive sampling. The total sample used in this study is 165 companies. Hypothesis testing is done with Ordinary Least Square (OLS) regression analysis on the first hypothesis and Moderated Regression analysis (MRA) on the second hypothesis. The results of this study show that business group affiliation has a significant positive effect on earnings management and audit quality is able to weaken the association between business group affiliation and earnings management.